REVISI SANKSI DENDA ADMINISTRATIF MENURUT HUKUM PERSAINGAN USAHA INDONESIA PASCA UNDANG-UNDANG CIPTA KERJA : SUATU ANALISIS HUKUM - Apriani, Desi; Idris, Zulherman; Kurniasih, Esy; Sinaga, Pandu (LPPM, Universitas Muhammadiyah Riau, 2025)
After the Job Creation Law, there have been substantive changes to Indonesia's business competition law,one of which is related to administrative sanctions in the form of fines. The change in the fine sanctionwas then followed up through a government regulation which actually caused confusion about themaximum fine limit and caused criticism from business economic observers of the law of competition, soit is necessary to conduct in-depth research from the aspect of legal analysis to get answers to theconfusion and offer a conceptual solution towards an effective business competition law. This research isa normative legal research with a legislative, conceptual, and philosophical approach. Based on theresults of the research, it can be explained that the philosophy of changing the administrative finesanction is in line with the philosophy of the Job Creation Law, namely maintaining investment interestsand the interests of labor. However, legally and based on data, the provision of a maximum fine of only50% of net profit or 10% of sales turnover during the occurrence of a violation is seen as not having adeterrent effect in order to prevent the occurrence of monopoly practices and unfair business competitionas one of the objectives of the law. The author suggests that a more in-depth study be carried out on theformulation of administrative fine sanctions in the context of the development of business competition lawin the future by paying more attention to the interests of many parties.